Upaya pengembangan usaha mandiri di kalangan pengangguran terdidik di Jawa Timur - Bagong Suyanto; Septi Ariadi (Faculty of Social and Political Science, Universitas Airlangga, 2015)
The report study intends to examined several obstacles faced by the graduates of the Faculty of Economics and Business in developing their entrepreneurship, mapping their networking, and formulating contextual intervention program in order to accelerate effort to handle unemployment problem. Data were collected by in-depth interview. After undergo editing and classification processes, data were analyzed and interpreted. The study shows that, even the economic graduates are those who have graduated from a well-known university with GPA were at least of 3.00, they generally do not have the ability and ambision to develop independent business or entrepreneurship. Various theories and experiences which were given during the study in college are generally considered to be less supportive in entrepreneurship development. In many cases, the graduates of the Faculty of Economics and Business prefer to work for someone else. One of the constraint that often encountered by the graduates of Faculty of Economics and Business were the lack of capital and excessive competitor in the field. There was an urgency to improve curriculum and study activity to provide a better media for student to learn entrepenuership.